Liver resection versus radiofrequency ablation for hepatocellular carcinoma: A systemic review and meta-analysis - He, Zheng; Song, Guolang; Yang, Guangchao; Fu, Xuan; Tian, Meng; Zhu, Yanhui (Frontiers in Oncology, 2025)
BackgroundLiver resection and radiofrequency ablation (RFA) are two common treatments for hepatocellular carcinoma (HCC). However, their efficacy and safety remain unclear. We aimed to conduct a systematic review and meta-analysis to compare the effectiveness and safety of these two treatments.MethodsWe searched multiple databases to identify randomized controlled trials (RCTs) that compared liver resection with RFA for the treatment of HCC. The primary outcome was 5-year overall survival rate. The secondary endpoint was the incidence of complications. We used RevMan 5.4 software to calculate the pooled effects and 95% confidence interval (CI).ResultsTen RCTs and 35 cohort studies were included in this meta-analysis. The pooled OR for 5-year overall survival rate favored liver resection (OR = 1.76, 95% CI = 1.19-2.61, P<0.00001). RFA was indicated with less postoperative complications (OR = 3.35, 95% CI = 2.52-4.45, P<0.00001).ConclusionThis meta-analysis suggests that liver resection is more effective than RFA in treating HCC with regard to higher 5-year overall survival rate, while the safety of liver resection was concerning. We recommend liver resection as a first-line treatment for HCC, but RFA may be a preferable choice for patients who are not suitable for surgical procedures. More high-quality RCTs are needed to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025458621.